2017
DOI: 10.1016/j.pmedr.2016.10.015
|View full text |Cite
|
Sign up to set email alerts
|

Local food environment and fruit and vegetable consumption: An ecological study

Abstract: Ecological studies are essential for understanding the environment-diet relationship. The purpose of this study was to describe environmental conditions and their relationship with fruit and vegetable (FV) consumption among Brazilian public health service users in the city of Belo Horizonte. We evaluated food stores contained within 1600 m buffer zones at 18 Health Academy Programme sites, from 2013 to 2014. Variables at the community (density, proximity and type) and the consumer (sectional location of FV; av… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
46
0
11

Year Published

2018
2018
2023
2023

Publication Types

Select...
7
1
1

Relationship

2
7

Authors

Journals

citations
Cited by 49 publications
(58 citation statements)
references
References 26 publications
1
46
0
11
Order By: Relevance
“…Também não foram avaliados os estabelecimentos de comercialização de alimentos para consumo imediato. Entretanto, o estudo de Bezerra et al (2013, apud Menezes et al 37 ) verificou que 40% da população brasileira consomem alimentos fora do domicílio, sendo este consumo menor em idosos (18,9%), mulheres (39,5%) e indivíduos com menor renda (36%). Neste trabalho, a unidade de análise foi o território com PAS, de Belo Horizonte, no qual os usuários são, em sua maioria, mulheres (88,1%), com idade média de 56,7 ± 11,8 anos (56,6% eram adultos mais velhos e 43,4% eram idosos), com baixo nível educacional (7,2 ± 4,1 anos) e renda mensal per capita [R$ 678,0; P 25 -P 75 :423,8-1000,0] 37 .…”
Section: Figuraunclassified
“…Também não foram avaliados os estabelecimentos de comercialização de alimentos para consumo imediato. Entretanto, o estudo de Bezerra et al (2013, apud Menezes et al 37 ) verificou que 40% da população brasileira consomem alimentos fora do domicílio, sendo este consumo menor em idosos (18,9%), mulheres (39,5%) e indivíduos com menor renda (36%). Neste trabalho, a unidade de análise foi o território com PAS, de Belo Horizonte, no qual os usuários são, em sua maioria, mulheres (88,1%), com idade média de 56,7 ± 11,8 anos (56,6% eram adultos mais velhos e 43,4% eram idosos), com baixo nível educacional (7,2 ± 4,1 anos) e renda mensal per capita [R$ 678,0; P 25 -P 75 :423,8-1000,0] 37 .…”
Section: Figuraunclassified
“…Based on simple conglomerate sampling, stratified by the nine administrative regions of the municipality, two units of the PAS of each region were randomly selected, totaling 18 units. Further details on sampling can be found in Menezes et al [20].…”
Section: E T H O D Smentioning
confidence: 99%
“…Neighborhood social disadvantage is another contextual characteristic related to obesity. Socially disadvantaged neighborhoods tend to have a lower availability of healthy foods when compared to more advantaged neighborhoods 29,30,31,32,33,34,35,36,37 . Menezes et al 35 , when evaluated Brazilian adults found that average consumption of fruits and vegetables was higher in neighbourhoods with higher income and concentration of food stores.…”
Section: Introductionmentioning
confidence: 99%
“…Socially disadvantaged neighborhoods tend to have a lower availability of healthy foods when compared to more advantaged neighborhoods 29,30,31,32,33,34,35,36,37 . Menezes et al 35 , when evaluated Brazilian adults found that average consumption of fruits and vegetables was higher in neighbourhoods with higher income and concentration of food stores. Furthermore, studies exploring the relationship between the food environment and obesity suggest that higher access to healthy food is associated with better diet quality and lower rates of obesity 26,29,38,39,40 .…”
Section: Introductionmentioning
confidence: 99%